Smitten : sex, gender, and the contest for souls in the Second Great Awakening - Hessinger, Rodney (Cornell University Press, 2022)
"This work investigates the experience of enthusiastic religion in early-nineteenth-century America, particularly among the Mormons, Shakers, Catholics, Methodists, Baptists, and Oneida Perfectionists. It reveals how religious competition produced sexual and gender disruptions during the Second Great Awakening, highlighting the subsequent domestication of religion in response to these challenges"--